An adapted imaginal exposure approach to traditional methods used within trauma-focused cognitive behavioural therapy, trialled with a veteran population. (1st June 2016) - Kaur, Manveer; Murphy, Dominic; Smith, Kirsten V.
Abstract: Trauma-focused cognitive behavioural therapy (TF-CBT) is beneficial for individuals with post-traumatic stress disorder (PTSD); however, a subset of clients struggle to engage with traditional methods, due to high levels of avoidance and dissociation. This paper aims to describe an adapted approach to imaginal reliving and prolonged exposure, to facilitate subsequent cognitive updating. The paper demonstrates the technique with veterans, who are a client group that may struggle with some aspects of traditionally implemented TF-CBT. Two case studies are described, both with PTSD symptoms stemming from traumatic military experiences. An adapted exposure technique is utilized to address the barriers of high dissociation, poor access to trauma-related cognitions and fixed intrusive imagery. The approach involved three stages: (1) reliving the trauma outdoors, (2) manipulating the perspectives of the imagery, and (3) restructuring the narrative with new perspectives. Both clients showed decreased dissociation and improved toleration of their traumatic imagery. Improvement of PTSD symptoms and quality-of-life functioning was observed for both clients on objective measures. Adapting TF-CBT to have a stronger emphasis on grounding and allocentric processing may be helpful for a subset of patients with PTSD that present with high levels of dissociation and avoidance. Further research and investigation into alternative populations is needed.